Respuesta :

Answer:

Step-by-step explanation:

4x + 5y = 6 -----------(I)

y = -5x - 3 --------(II)

Substitute y = -5x - 3 in equation (I)

4x + 5 (-5x - 3) = 6

4x - 25x - 15 = 6

Add 15 to both sides

4x - 25x  = 6 + 15

Combine  like terms

-21x = 21

Divide both sides by (-21)

x = 21/(-21)

x = -1

Substitute x = - in equation (II)

y = -5(-1) - 3

   = 5 - 3

y = 2

Solutions (-1 , 2)

2) -3x + y = 2-------------(I)

-x + y - 4 = 0

      y = 4 + x    ------------(II)

Substitute y  = x + 4 in equation (I)

-3x + x + 4 = 2

-3x + x = 2 - 4

Combine like terms

-2x = -2

Divide both sides by (-2)

x = (-2)/(-2)

x = 1

Substitute x = 1 i n equation (II)

y = 4 + 1

y = 5

Solution (1,5)

3)  5x + 2y = 5 ------------(I)

y = -2x + 3 ------------(II)

Substitute y = -2x + 3 in equation (I)

5x + 2*(-2x + 3) = 5

5x - 4x + 6 = 5

5x - 4x = 5 - 6

Combine like terms

x = -1

Substitute x = -1 in equation (II)

y = (-2)*(-1) + 3

   = 2 + 3

y = 5

Solution: ( -1 , 5)